LEGAL MEMORANDUM TENTANG WANPRESTASI: ANALISIS PUTUSAN PENGADILAN TINGGI SEMARANG Nomor 460/PDT/2020/ PT SMG - Syaharani, Nabilah; Fitrianto, Bambang; Nurdiana, Citra; Saputra, Defri Dwi; Harahap, Rizki Nanda Fauzi (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
This study examines a breach of contract case in a lease agreement, as reflected in the Decision of the Semarang High Court Number 460/PDT/2020/PT SMG. The dispute originated from the Plaintiff's claim that the Defendant had failed to pay the remaining lease amount of Rp 40.000.000. However, the Defendant successfully demonstrated that an overpayment of Rp 20.000.000 had occurred beyond the agreed contractual obligation. Additionally, the Defendant raised an exception regarding the absence of necessary parties (Plurium Litis Consortium), arguing that the Plaintiff had acted individually without including other heirs of the leased property, which was part of an inherited estate. This research adopts a normative juridical method with statutory and case approaches. Data were drawn from primary and secondary legal materials and analyzed qualitatively using a descriptive approach. The analysis reveals that the panel of judges upheld the Defendant’s exception and declared the Plaintiff’s claim inadmissible (Niet Ontvankelijke Verklaard), without proceeding to the merits of the case, on the grounds of a formal defect. Furthermore, the claim was considered obscuur libel (vague), as it failed to specify the legal basis for the alleged breach of contract. This study underscores the importance of fulfilling formal requirements in civil litigation, including clarity in the content of the claim and completeness of the involved parties, to preserve the right to substantive examination. The decision provides a valuable legal lesson on the critical role of documentation, evidence, and the structural formulation of a lawsuit in upholding justice in civil cases.